Collaborative story development across the creative arts and nursing: reflections on a practice-based filmmaking research project. Issue 4 (2nd October 2022) - Cattoni, Jan; Ryan, Colleen; Batty, Craig; McAllister, Margaret; Nash, Joshua
ABSTRACT: This article describes an interdisciplinary creative collaboration between a group of academic researchers from the creative arts and nursing education, along with professional actors, who co-created a series of short film scenarios for pedagogic impact. The scenarios were intended to improve the experiences of nursing students on placement by supporting nurse educators to experiment with a transformative learning praxis in their pre-and post-placement interactions with students. This work addresses the process of collaborative content creation, which was undertaken through a method comprising character and story development drawn from screenwriting, improvisation and (Creative) Participatory Action Research. Beyond influencing nursing pedagogy, we suggest this approach has useful implications for creative practice disciplines more broadly, and the application of story development scenarios across a range of academic contexts for pedagogic impact.